Ambient aromatic hydrocarbon measurements at Welgegund, South Africa - K. Jaars; J. P. Beukes; P. G. van Zyl; A. D. Venter; M. Josipovic; J. J. Pienaar; V. Vakkari; H. Aaltonen; H. Laakso; M. Kulmala; P. Tiitta; A. Guenther; et al. (Atmospheric Chemistry and Physics, 2014)
Aromatic hydrocarbons are associated with direct adverse human health effects and can have negative impacts on ecosystems due to their toxicity, as well as indirect negative effects through the formation of tropospheric ozone and secondary organic aerosol, which affect human health, crop production and regional climate. Measurements of aromatic hydrocarbons were conducted at the Welgegund measurement station (South Africa), which is considered to be a regionally representative background site. However, the site is occasionally impacted by plumes from major anthropogenic source regions in the interior of South Africa, which include the western Bushveld Igneous Complex (e.g. platinum, base metal and ferrochrome smelters), the eastern Bushveld Igneous Complex (platinum and ferrochrome smelters), the Johannesburg–Pretoria metropolitan conurbation (> 10 million people), the Vaal Triangle (e.g. petrochemical and pyrometallurgical industries), the Mpumalanga Highveld (e.g. coal-fired power plants and petrochemical industry) and also a region of anticyclonic recirculation of air mass over the interior of South Africa. The aromatic hydrocarbon measurements were conducted with an automated sampler on Tenax-TA and Carbopack-B adsorbent tubes with heated inlet for 1 year. Samples were collected twice a week for 2 h during daytime and 2 h during night-time. A thermal desorption unit, connected to a gas chromatograph and a mass selective detector was used for sample preparation and analysis. Results indicated that the monthly median (mean) total aromatic hydrocarbon concentrations ranged between 0.01 (0.011) and 3.1 (3.2) ppb. Benzene levels did not exceed the local air quality standard limit, i.e. annual mean of 1.6 ppb. Toluene was the most abundant compound, with an annual median (mean) concentration of 0.63 (0.89) ppb. No statistically significant differences in the concentrations measured during daytime and night-time were found, and no distinct seasonal patterns were observed. Air mass back trajectory analysis indicated that the lack of seasonal cycles could be attributed to patterns determining the origin of the air masses sampled. Aromatic hydrocarbon concentrations were in general significantly higher in air masses that passed over anthropogenically impacted regions. Inter-compound correlations and ratios gave some indications of the possible sources of the different aromatic hydrocarbons in the source regions defined in the paper. The highest contribution of aromatic hydrocarbon concentrations to ozone formation potential was also observed in plumes passing over anthropogenically impacted regions.